Expression of c-erbB3 protein in primary breast carcinomas. - Naidu, R.; Yadav, M.; Nair, S.; Kutty, M.K. (Nature Publishing Group, 1998)
Expression of c-erbB3 protein was investigated in 104 primary breast carcinomas comprising nine comedo ductal carcinoma in situ (DCIS), 91 invasive ductal carcinomas and four invasive lobular carcinomas using two monoclonal antibodies, RTJ1 and RTJ2. Of the 91 invasive ductal carcinomas, seven contained the comedo DCIS component adjacent to the invasive component. An immunohistochemical technique was used to evaluate the association between expression of c-erbB3 and clinical parameters and tumour markers such as epidermal growth factor receptor (EGFR), c-erbB2, cathepsin-D and p53 in archival formalin-fixed paraffin-embedded tumour tissues. Our results indicated that RTJ1 and RTJ2 gave identical staining patterns and concordant results. It was found that the overexpression of c-erbB3 protein was observed in 67% (6/9) of comedo DCIS, 52% (44/84) of invasive ductal carcinomas, 71% (5/7) of carcinomas containing both the in situ and invasive lesions and 25% (1/4) of invasive lobular carcinomas. A significant relationship (P < 0.05) was observed between strong immunoreactivity of c-erbB3 protein and histological grade, EGFR and cathepsin-D, but not with expression of c-erbB2, p53, oestrogen receptor status, lymph node metastases or age of patient. However, we noted that a high percentage of oestrogen receptor-negative tumours (59%), lymph node-positive tumours (63%) and c-erbB2 (63%) were strongly positive for c-erbB3 protein. We have also documented that a high percentage of EGFR (67%), c-erbB2 (67%), p53 (75%) and cathepsin-D-positive DCIS (60%) were strongly positive for c-erbB3. These observations suggest that overexpression of c-erbB3 protein could play an important role in tumour progression from non-invasive to invasive and, also, that it may have the potential to be used as a marker for poor prognosis of breast cancer.